Do tadpoles vanish in the light-front? - Suzuki, Alfredo Takashi [UNESP]; Carrillo, Luis Alberto S. [UNESP]; Oliveira Sales, Jorge Henrique [UNESP] (Elsevier B.V., 2010)
In covariant gauges (CG) regularized with dimensional regularization (DR) it is a standard procedure to set all tadpole Feynman integrals to zero, though; explicitly, they diverge quadratically as the space-time volume. on the other hand, in the notoriously subtle light-front gauge (LTG) some divergent tadpole integrals are said to be nonvanishing, i.e., cannot be set to zero as in the CC case. In this article we analyse the reasons behind this seemingly ambiguous results.